Engineering and Technology Challenges of The Energy Usage: An Estimation for Agro-Industrial In Indonesia. Issue 1 (June 2020) - Asnawi, Y H; Nuraisyah, A; Zulfiandri,; Sari, V I; Rahmawati,; Gunawan,; Rahmana, A
Abstract: Agro industry is one of strategic industry that supported by a potencial resources from agriculture, fisheries/marine, livestock, farm, and forestry sectors. Energy supply with affordable prices are factors of the agro industry sustainability. The purpose of this study is to ensure the availability of energy in the agriculture industries, the pulp & paper industries, the sugar industries from sugar cane, and the fish canning industries. The stages consist of identifying the needs and availability of raw materials, energy, and formulating the recommendations. A literature study from relevant sources and analysis of efficiency of energy is used to improve the industry competitiveness by using Net Energy Ratio (NER) calculation. Around 38% of the agro industries energy needs are from by-product's biomass. Biomass fuels that usually using by agro industries are palm shells, wood chips, bagasse, black liquor, or depending on the by-products. Aggregately, agro industries energy needs (2017) amounted to 15, 711 million TOE. Based on the capacity, the final energy needs of selected agro industries amounted to 25, 818 millions TOE that equivalent to 11% from the national final energy demand of 238.8 millions TOE and 30% of the final industrial sector energy needs of 87 millions TOE in 2025.